A novel spermatozoan ultrastructure in the shrimp Hippolyte obliquimanus Dana, 1852 (Decapoda: Caridea: Hippolytidae) - Terossi, Mariana (2012)
The aim of this study was to describe and illustrate the morphology of the spermatozoon of the Western Atlantic shrimp, Hippolyte obliquimanus. Individuals were sampled from Itaguá Beach (Ubatuba, southern Brazil). The male reproductive system was dissected and morphological analysis was undertaken using a stereomicroscope, a light microscope, and transmission electron and scanning electron microscopes. When viewed from the nuclear or acrosomal poles, each spermatozoon has many translucent radiating arms (about 20) from a denser cell body, while laterally the cell body and arms resemble a “cnidarian medusa”, with all the arms projecting away from the bell-like cell body. This sperm morphology is distinct from the “thumbtack”-shaped spermatozoa observed in the majority of carideans but has similarities to the spermatozoa of Rhynchocinetes spp. The morphology of sperm of several species of the genus Hippolyte resembles the spermatozoon of H. obliquimanus with the presence of posterior nuclear arms, but it is necessary to study other Hippolyte species to place these arms in the context of the genus.